Laboratory practices in the teaching of basic biomedical sciences. Before or after seminars? - Sandra Williams Serrano; Luis Alberto Mass Sosa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
This article raises the need to reflect on laboratory practice location in the program of basic biomedical subjects. Some elements are offered about the benefits of this organizational form so that students acquire procedural knowledge and develop capacities that allow more cognitive independence, especially in more advanced semesters of the academic program. New questions are made about whether this positioning could modify or not, the teacher´s position as a classroom researcher and consequently exercise autonomous influences for the development of the aforementioned abilities in the students, in accordance with the requirements of the new academic formation plans.